Nitric Oxide Releasing Nanoparticles as a Strategy to Improve Current Onychomycosis Treatments - Costa-Orlandi, Caroline B. [UNESP]; Mordorski, Breanne; Baltazar, Ludmila M.; Mendes-Giannini, Maria Jose S. [UNESP]; Friedman, Joel M.; Nosanchuk, Joshua D.; Friedman, Adam J. (Journal Of Drugs In Dermatology, 2018)
Topical antimicrobials are the ideal mode of onychomycosis treatment for efficient drug delivery and avoidance of sytemic effects associated with oral medications. However, high treatment costs, tissue penetration limitations, and low cure rates have continued to pose major challenges. To capitalize on the progress made by topical efinaconazole solution, efinaconazole was combined with inexpensive, previously-characterized nitric oxide releasing nanoparticles (NO-np), which have been shown to offer sustained nitric oxide release over time and enhanced barrier penetration, while exerting broad spectrum antimicrobial and immunomodulating properties. NO-np were combined with efinaconazole in varying concentrations and applied against reference strains of Trichophyton rubrum using a checkerboard method. Results demonstrated synergism of NO-np+efinaconazole against T rubrum, which is noteworthy given the barriers present in the topical treatment of onychomycosis, and the multiple potential benefits offered by NO-np. Overall, this study illustrates the untapped potential of nanotechnology in the treatment of disorders of the skin, hair, and nails where drug delivery remains a challenge.